Using CORBA to integrate a compiler developed in Java with tools in other programming languages (Revista Brasileira de Contabilidade e Gestão, 2013)
This article presents a solution for integrating the core of a compiler built using the Java language with other programming languages. Were analyzed different alternatives of integration and it was decided to use CORBA for it best meet of the desired requirements. All the core features were provided to other applications using CORBA. It was performed a case study of integration with an IDE built in C # which allowed the validation of the implementation and pointed performance problems that deserve further investigation.
Keywords: compiler; CORBA; interoperability